In-plane shear strengthening of brick masonry panel with geogrid reinforcement embedded in bed and bed-head joints mortar. (15th January 2021) - Behera, Biplab; Nanda, Radhikesh Prasad
Highlights: Masonry wall can be strengthened with bed joint reinforcement. Geogrid embedded mortar enhances the mortar capacity. Better in-plane shear strength, crushing values, ductility etc than un-reinforced wall. Easy to construct with economy. Abstract: An experimental investigation was carried out to study the strengthening performance of brick masonry prisms and panels via geogrid reinforcement embedded in brick mortar. A compressive strength test was performed for brick prisms, while a diagonal compression test was performed for brick panel with two patterns, i.e., geogrid reinforcement at bed joints as well as at bed-head joints. The compressive strength of the geogrid embedded prisms was found to be 32.65% more than that of un-reinforced brick prisms. While, geogrid-reinforced brick panels exhibited better crushing load, in-plane shear strength, lateral strength, ductility, etc., than un-reinforced masonry with the highest in-case of bed joint reinforcement. Cost analysis showed that the unit costs of un-reinforced and reinforced walls are similar (within 6.5%). Thus strengthened walls can be valid alternative to un-strengthened walls for new constructions and a low-cost strengthening technique for earthquake disaster mitigation of brick masonry buildings.